Modern Methods of Using Magnets in Medicine (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Based on the development of science and technology, new achievements in medicine are being achieved. In recent years, the Ministry of Health has developed methods for using magnets in various pillars. Currently, magnetic ones are widely used in diagnostics, therapy and other areas are effectively used.